Hubungan Pengetahuan Tentang Menarche dengan Tingkat Kecemasan Putri Remaja Awal di Wilayah Kerja Puskesmas Pantai Labu Tahun 2024 - Sri Rahmayani; Ester Simanullang; Rumondang Sitorus (Inovasi Kesehatan Global, 2024)
Menarche is the first menstruation that usually occurs between the ages of 10 and 16 years, or in early adolescence in the middle of puberty, just before the reproductive period begins. The aim of this research is to analyze the relationship between knowledge about Menarch and the anxiety level of early teenage girls in the working area of the Pumpkin Beach Public Health Center. 2023. This research uses analytical descriptive research which aims to systematically and factually describe the facts and relationships between communicating variables by collecting data, processing, analyzing and interpreting data in statistical hypothesis testing. The sampling technique used was total sampling. The instrument used was a questionnaire and analysis of the results of the chi-square statistical test concluded that p-value = 0.003 or <0.05, so a significant relationship was found between the level of knowledge. with the level of anxiety of teenagers in facing menarche in the work area of the Pumpkin Beach Community Health Center in 2023